2017
DOI: 10.1155/2017/2494067
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Hypertension Resulting from Fructose Enriched Diet in Wistar Rats

Abstract: Increased sugar consumption, especially fructose, is strongly related to the development of type 2 diabetes (T2D) and metabolic syndrome. The aim of this study was to evaluate long term effects of fructose supplementation on Wistar rats. Three-week-old male rats were randomly divided into 2 groups: control (C; n = 14) and fructose fed (FF; n = 18), with a fructose enriched drink (20–25% w/v fructose in water) for 21 weeks. Systolic blood pressure, fasting glycemia, and bodyweight were regularly measured. Gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
37
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 48 publications
11
37
0
4
Order By: Relevance
“…In our study, elevated caloric intake related to fructose overconsumption was not followed by an increase in body mass. Similar findings were reported in some previously published studies [7,[25][26][27], while other authors have reported an increase in body mass [28,29]. These discrepancies could be attributed to differences in experimental settings, such as treatment duration, fructose concentration and the form in which the fructose was consumed (liquid vs. solid food), as well as the age of the experimental animals.…”
Section: Controlsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, elevated caloric intake related to fructose overconsumption was not followed by an increase in body mass. Similar findings were reported in some previously published studies [7,[25][26][27], while other authors have reported an increase in body mass [28,29]. These discrepancies could be attributed to differences in experimental settings, such as treatment duration, fructose concentration and the form in which the fructose was consumed (liquid vs. solid food), as well as the age of the experimental animals.…”
Section: Controlsupporting
confidence: 87%
“…Some authors have suggested that fructose overconsumption is associated with increased risk of obesity, insulin resistance, metabolic syndrome, type 2 diabetes, cardiovascular disease and nonalcoholic fatty liver disease [1][2][3], with other authors not fully supporting these assertions [4][5][6]. Studies performed on animals have shown that fructose supplementation can result in hypertension, insulin resistance, dyslipidemia and the accumulation of visceral and ectopic fat [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although diets high in fructose or fat and fructose (HFHF) have been reported to increase fBGLs in male rats at 3 and 8 weeks (Dupas et al, 2017;Huang, Chiang, Yao, & Chiang, 2004;Wong et al, 2018), other studies have reported that fBGLs in male rats were unaltered 8 weeks following high-fructose feeding (Sanchez-Lozada et al, 2007) and 16 weeks following high-fat/high-sugar feeding (Gerbaix et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a diet high in fat and sugar on fBGLs is not clear. Although diets high in fructose or fat and fructose (HFHF) have been reported to increase fBGLs in male rats at 3 and 8 weeks (Dupas et al, ; Huang, Chiang, Yao, & Chiang, ; Wong et al, ), other studies have reported that fBGLs in male rats were unaltered 8 weeks following high‐fructose feeding (Sanchez‐Lozada et al, ) and 16 weeks following high‐fat/high‐sugar feeding (Gerbaix et al, ). Similarly, we did not observe a significant change in fBGLs in female rats on an HFHF diet.…”
Section: Discussionmentioning
confidence: 99%
“…The result of case-control research using wistar rats proved that rats were fed with fructose supplementation induced hypertension, insulin resistance, and dyslipidemia. Meanwhile, the rats in the control group did not (Dupas et al, 2017). Other studies proved that excessive fructose intake increases blood pressure in wistar rats of 7 ± 2 mm Hg (SBP) and 5 ± 2 mm Hg (DBP) (Perez et al, 2010).…”
Section: Introductionmentioning
confidence: 92%